An innovative model of university cooperation in developing countries: results of five years of experience in internal medicine, health promotion and education - Filomena Pietrantonio; Vera Kopsaj; Francesco Rosiello; Aurora Tomassoni; Luca Moriconi; Donatella Padua (Italian Journal of Medicine)
University cooperation in the field of humanitarian medicine combines academic expertise with development initiatives. The UniCamillus Task Force was established in 2019 to propose new models for training students from developing countries and promoting self-sufficient health systems through medical interventions, education, and capacity building. Five years of experience in regions such as the Amazon, Cameroon, and the Gambia, using assessments, stakeholder collaboration, training, and long-term monitoring, were used to create an innovative model. Data was collected through field reports, interviews, and impact evaluations. In five years, over 130 health workers were trained, telemedicine centers were established, and improved medical access for underserved populations was achieved. The missions have provided over 4000 consultations and ensured continuity of health facilities after surgery. Integrating university cooperation into development programs promotes sustainable health autonomy. By addressing the challenges of humanitarian medicine ̶ lack of coordination, inadequate follow-up, and inadequate technology – working with an innovative model strengthens health systems in the target regions. The innovative model of university cooperation exemplifies university-led humanitarian medicine, fusing research, education, and service. Future efforts will improve digital health solutions, expand research collaborations, and strengthen institutional networks for lasting impact.